RIYADUS SOLIHIN : TAMAN ORANG-ORANG SOLEH - Al-Nawawi, Imam, 1233-1277; Makbul; Raharusun, Agus, Dr.; Pahlevi, Reza, Dr.; Akhyar; Sastrawinata, Dahlan; Subhan Nurdin; Setiawan, Iwan; Hasrul Wahab; Mohamad Amiro Safwan; Norhayati Mat Kassem; Dini Handayani Hasan (Shah Alam, Selangor : Grup Buku Karangkraf Sdn. Bhd., 2017)
Mengandungi fadhilat amal, adab harian, didikan akhlak, penyucian hati, permasalahan ibadah dan kehidupan bermasyarakat
Contains verses from the Qur'an and quotes from the Hadith
Keywords: Religious life -- Islam; Islam -- Customs and practices; Muslims -- Conduct of life